2018
DOI: 10.1099/jgv.0.001104
|View full text |Cite
|
Sign up to set email alerts
|

Viruses of invasive Argentine ants from the European Main supercolony: characterization, interactions and evolution

Abstract: The Argentine ant (Linepithema humile) is a highly invasive pest, yet very little is known about its viruses. We analysed individual RNA-sequencing data from 48 Argentine ant queens to identify and characterisze their viruses. We discovered eight complete RNA virus genomes - all from different virus families - and one putative partial entomopoxvirus genome. Seven of the nine virus sequences were found from ant samples spanning 7 years, suggesting that these viruses may cause long-term infections within the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 61 publications
2
48
1
Order By: Relevance
“…In comparison to negative-and double-stranded viruses, RNA levels of positive-strand RNA viruses, such as LnoMLV1, varied most between the glow-worm individuals. Similar phenomenon has also been seen in Argentine ant viruses [36]. However, such massive LnoMLV1 levels as found in the two males are clearly a result of pathogenic virus activation and might explain why we did not detect LnoMLV1 the next year.…”
Section: Discussionsupporting
confidence: 83%
“…In comparison to negative-and double-stranded viruses, RNA levels of positive-strand RNA viruses, such as LnoMLV1, varied most between the glow-worm individuals. Similar phenomenon has also been seen in Argentine ant viruses [36]. However, such massive LnoMLV1 levels as found in the two males are clearly a result of pathogenic virus activation and might explain why we did not detect LnoMLV1 the next year.…”
Section: Discussionsupporting
confidence: 83%
“…An ONLV2-related endogenized virus element (EVE) has also been reported for arthropods (Shi et al 2016); EVEs represent virus fragments that have been spuriously reverse-transcribed and integrated into host genomes, and provide further evidence as to the true host(s) of virus groups (Katzourakis and Gifford 2010). We also detected sequences predicted to encode proteins with (Chandler et al 2015;Shi et al 2016;Shi et al 2017;Viljakainen et al 2018;Göertz et al 2019).…”
Section: Discussionmentioning
confidence: 61%
“…Eight RNA viruses were identified in the Trinity‐assembled contigs of reads that could not be mapped to the L. humile genome (Viljakainen, Holmberg, Abril, & Jurvansuu, ). We found that all our samples contained RNA viruses at different loads.…”
Section: Resultsmentioning
confidence: 99%